Aregs-IGFBP3-mediated SMC-like cells apoptosis impairs beige adipocytes formation in aged mice - Shifeng Wang; Yuanxu Cui; Limei Wang; Chun Feng; Yifei Sun; Bangyun Huo; Honglu Jiang; Mingyu Zhao; Yingying Tu; Qiyue Wang; Yutao Yang; Qiang Zhang (Molecular Metabolism)
Aging is associated with a decline in the browning capacity of white adipose tissue (WAT), contributing to metabolic dysfunction. Beige adipocytes, which dissipate excess energy as heat, are a key feature of this process. In this study, we investigate the role of adipose stem and progenitor cells (ASPCs), specifically the Aregs (CD142+) subpopulation, in regulating beige adipocyte formation in aged mice under cold stimulation. Our findings reveal that Aregs significantly increase in the subcutaneous WAT (sWAT) of aged mice following cold exposure. We further demonstrate that Aregs secrete insulin-like growth factor binding protein 3 (IGFBP3), which appears to play a pivotal role in the cross-talk between adipogenesis-regulatory cells (Aregs) and smooth muscle cell-like (SMC-like) cells, thereby leading to the inhibition of beige adipocytes formation. Functional enrichment analysis highlighted the activation of TGFβ, MAPK and p53 signaling pathways in SMC-like cells, all of which are known to induce cell apoptosis and fibrosis. Moreover, IGFBP3 was found to interact with receptors and signaling molecules, including Egfr, Irf1 and Cdkn1a, in SMC-like cells, enhancing their apoptosis. Co-culture experiments confirmed that IGFBP3 significantly suppressed the formation of beige adipocytes, further corroborating its role in impairing browning. Overall, our study provides novel insights into the molecular mechanisms by which Aregs and IGFBP3 contribute to the age-related decline in WAT browning. These findings suggest potential therapeutic targets for reversing impaired WAT browning in aging and related metabolic disorders.